Volume 5: Turbo Expo 2002, Parts a and B 2002
DOI: 10.1115/gt2002-30368
|View full text |Cite
|
Sign up to set email alerts
|

Self-Recirculating Casing Treatment Concept for Enhanced Compressor Performance

Abstract: A state-of-the-art CFD code (APNASA) was employed in a computationally based investigation of the impact of casing bleed and injection on the stability and performance of a moderate speed fan rotor wherein the stalling mass flow is controlled by tip flow field breakdown. The investigation was guided by observed trends in endwall flow characteristics (e.g., increasing endwall aerodynamic blockage) as stall is approached, and based on the hypothesis that application of bleed or injection can mitigate these trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 13 publications
0
50
0
Order By: Relevance
“…Casing treatment is a method that significantly improves the performance of a compressor/fan, and it has been developed into many forms since Koch C C [5][6][7][8][9] found that it can improve the compressor stability margin. The traditional casing treatment includes axial slots, circumferential grooves, and chordwise grooves [10][11][12][13][14][15][16]. Greitzer [10] concluded that the traditional casing treatment can extend the stall margin at the expense of efficiency loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Casing treatment is a method that significantly improves the performance of a compressor/fan, and it has been developed into many forms since Koch C C [5][6][7][8][9] found that it can improve the compressor stability margin. The traditional casing treatment includes axial slots, circumferential grooves, and chordwise grooves [10][11][12][13][14][15][16]. Greitzer [10] concluded that the traditional casing treatment can extend the stall margin at the expense of efficiency loss.…”
Section: Introductionmentioning
confidence: 99%
“…Considering both the efficiency and the stall margin, Hathaway [16] proposed a self-recirculating casing treatment that, unlike the conventional casing treatment, has an external airflow path isolated from the compressor main flow. The downstream high pressure is sucked by the slot and then driven by the differential pressure before being ejected from the leading edge of the blade through the external airflow channel.…”
Section: Introductionmentioning
confidence: 99%
“…In their experiments, they found that simpler casing treatments, without bleed flow, might provide appreciable improvements in the stall range. Many researchers have been studying the casing treatment on the axial compressor since early 1970s [4][5][6][7][8]. Later on the application to centrifugal compressors was carried out [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Tip injection has also been demonstrated as an effective tool for recovering a compressor from fully developed stall. In a self-induced (passive) solution, steady discrete tip injection using casing recirculation has been simulated in a single transonic fan rotor (Hathaway, 2002). The idea was to bleed pressurized fluid from downstream of the rotor and properly inject it upstream.…”
Section: Air Injectionmentioning
confidence: 99%